Measuring impacts of patient and public involvement and engagement (PPIE): a narrative review synthesis of review evidence - William Lammons; Anne L. Buffardi; Dalya Marks (Research Involvement and Engagement)
Abstract Introduction Patient and public involvement and engagement (PPIE), in its various forms, offers a wide range of potential benefits to research, health services and systems, and to those involved in this collaborative process. As PPIE has expanded over the years, so too have expectations regarding the evaluation of its effects and impacts. Methods We conducted a narrative review synthesis of review articles around measurement of PPIE impact – conceptualising ‘impact’ to include any type of effect on people or processes, both proximate and longer-term. We searched PubMed, Cochrane Library of Systematic Reviews, and CINAHL electronic databases and conducted hand searches. Inclusion criteria comprised: public involvement, reporting impacts of public involvement, and using a review methodology. This yielded 27 review articles based on studies in the UK, US, Canada and Australia. We employed a three-part analysis process: 1) extracting all subcategories of impact reported into Excel (n = 37); 2) combining and categorising this list into primary and subcategories of impact based on thematic analysis; and 3) cross-checking these categories with the original review. Results Our review of reviews indicates that studies often do not report impacts of PPIE activities and when they do, they report a wide range, with little consistency across studies. We classified four broad types of PPIE impacts on: people (PPIE contributors, researchers, healthcare staff and policymakers), different phases of the research process, services and systems and on PPIE processes themselves. Across these categories, the most commonly documented impacts relate to impacts on PPIE collaborators, including individual empowerment and recovery, on researchers, improving their understanding of and collaboration with people typically excluded from research and on earlier phases of the research process. Studies reported both positive and negative impacts. Methodologically, previous evaluations of PPIE impact predominantly relied on retrospective self-reporting, with little triangulation from other data sources or prospective data collection over time. Conclusion The impacts of PPIE appear to be under- and inconsistently reported. More robust evaluation of PPIE impact, drawing on the broad categories we present, offers opportunities for PPIE contributors, researchers and funders to better understand the effects of these investments.